Predicting fitness to drive of people with dementia in Iraq - Rashid, Roshe (2020)
Dementia causes progressive loss of cognitive capacities including memory, orientation, information processing, comprehension, insight and judgment. Thus, it leads to an impairment in activities of daily living and social functioning. Dementia affects driving performance and safety. People with dementia need to consider giving up their driving privileges at some point during the illness progression. However, driving cessation can result in loss of independence, mobility and social integration. Assessment of fitness to drive in drivers with dementia is important in maintaining patients’ rights and public safety. Cognitive tests are frequently used to inform recommendations on fitness to drive in people with dementia.